Incorporation of Heterocycles into Combinatorial Chemistry - Babaev, Eugene V. (SpringerBriefs in Molecular Science,, 2017)
The author has summarized a decade of teaching combinatorial chemistry into this timely brief. The solid phase synthesis of unnatural heterocyclic alpha-amino acids is illustrated by practical examples starting from the ABCs of peptide synthesis explored in chapter one. Chapter two is concerned with the solid phase synthesis which is shown on various techniques - BillBoard, tea-bag, and Lantern devices, and demonstrated on heterocyclic examples and protocols. In the third chapter the tools for accelerating chemical synthesis - solid phase and liquid phase - are reviewed. Here the techniques of parallel refluxing (including microwave and flow technique) and parallel separation (filtration, centrifugation, evaporation, and chromatography) are described. In the chapters 4 and 5 the author goes on to describe how the liquid phase synthesis of heterocycles (reductive amination and Ugi reaction of heterocycles) is illustrated with the use of semi-automated protocols. Finally, the design of combinatorial libraries of heterocycles is reviewed including the original author's findings.